Method for preparing nano-graphite microchip by adopting hydrodynamic cavitation and application of nano-graphite microchip
The preparation of nanographite microsheets through turbine hydraulic cavitation technology solves the problems of complex processes, high energy consumption and low yield in the existing technology, and achieves efficient and low-cost preparation and application expansion of nanographite microsheets.
Patent Information
- Application Number
- CN202411663110.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nanographite microsheet preparation methods have problems such as complex process, high energy consumption, low yield, low purity and uncontrollable size.
Turbo hydraulic cavitation technology is used to process expandable graphite into nanographite microsheets. By adjusting the outlet pressure and rotation speed, the particle size and surface area of the nanographite microsheets are controlled to avoid agglomeration.
It realizes efficient preparation of nanographite microsheets, adjustable particle size and surface area, high yield and low cost, and expands the application range of nanographite microsheets.
Smart Images

Figure CN119461360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method and application of nano graphite microsheets. Background Art
[0002] The main methods for preparing nanographite flakes include ball milling, ultrasonic crushing, laser pulse method, electrochemical method, etc. Among them, the laser pulse equipment is complex and has high energy consumption; the electrochemical method has high product purity and simple operation, but the yield is very low; the ball milling process is simple and low cost, but it mostly uses flake graphite as raw material, and the exfoliated nanographite flakes are prone to agglomeration, and the size of the nanographite flakes cannot be controlled.
[0003] The present invention adopts a method for preparing nanographite microsheets by turbine-type hydraulic cavitation. Hydraulic cavitation is a fluid mechanics phenomenon. When the bubbles generated by the fluid during the cavitation process move and collapse in the liquid, local high temperature and high pressure, light emission, discharge, strong shock waves, high-speed jets and other extreme conditions are generated, which produce high-intensity shear force on the expanded graphite in the expanded graphite suspension, forming a high-frequency alternating water pressure, so that the cavity expands and explodes to break the expanded graphite.
[0004] The present invention uses expandable graphite as a raw material to prepare nanographite microsheets, which meet the quality requirements of expandable graphite in different fields. In addition, the present invention further expands the application scope of the prepared nanographite microsheets, prepares them into graphite microsheets / ZnNiMn-LDH composite materials, and uses them as electrodes of supercapacitors, which is of great significance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing nano-graphite microsheets by using hydrodynamic cavitation and its application.
[0006] A method for preparing nanographite microsheets by hydrodynamic cavitation is specifically completed by the following steps:
[0007] 1. Using expandable graphite as a raw material, drying the expandable graphite to obtain dry expandable graphite;
[0008] 2. Put the dried expandable graphite into a microwave oven and perform microwave treatment for a period of time to obtain expanded graphite;
[0009] 3. Mix the expanded graphite, deionized water and additives evenly to obtain a suspension solution;
[0010] The mass ratio of deionized water to expanded graphite in step 3 is (45-55):1;
[0011] The auxiliary agent described in step 3 is anhydrous ethanol or polyethylene glycol;
[0012] The mass ratio of the additive and the expanded graphite described in step 3 is (0.5-2):1;
[0013] Fourth, adding the suspension solution into a turbine hydraulic cavitation generator, adjusting the outlet pressure and speed of the turbine hydraulic cavitation generator, the expanded graphite in the solution is peeled off under the action of cavitation force, the cavitation treatment is repeated, and then filtered and dried to obtain nanographite microsheets;
[0014] The nanographite flakes described in step 4 have a lateral size of 1 μm to 200 μm, a longitudinal size of 50 nm to 200 nm, and a surface area of 45 m 2 / g~80m 2 / g.
[0015] The nano graphite microsheets are used to prepare graphite microsheet / ZnNiMn-LDH composite materials.
[0016] Advantages of the present invention:
[0017] 1. The present invention uses expandable graphite as a raw material and adopts a turbine-type hydraulic cavitation generator to prepare nanographite microsheets; by: selecting expandable graphite of a certain expansion volume, additives and adjusting the outlet pressure and speed of the turbine-type hydraulic cavitation generator, graphite microsheets with different particle sizes and surface areas and without agglomeration can be obtained;
[0018] Second, the method of the present invention is simple and low-cost;
[0019] 3. The specific capacitance of the graphite microsheet / ZnNiMn-LDH composite material prepared by the present invention can reach 1958F / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a preparation flow chart of a method for preparing nano-graphite microsheets by using hydrodynamic cavitation. DETAILED DESCRIPTION
[0021] Specific implementation method 1: This implementation method is a method for preparing nanographite microsheets using hydrodynamic cavitation, which is specifically completed in the following steps:
[0022] 1. Using expandable graphite as a raw material, drying the expandable graphite to obtain dry expandable graphite;
[0023] 2. Put the dried expandable graphite into a microwave oven and perform microwave treatment for a period of time to obtain expanded graphite;
[0024] 3. Mix the expanded graphite, deionized water and additives evenly to obtain a suspension solution;
[0025] The mass ratio of deionized water to expanded graphite in step 3 is (45-55):1;
[0026] The auxiliary agent described in step 3 is anhydrous ethanol or polyethylene glycol;
[0027] The mass ratio of the additive and the expanded graphite described in step 3 is (0.5-2):1;
[0028] Fourth, adding the suspension solution into a turbine hydraulic cavitation generator, adjusting the outlet pressure and speed of the turbine hydraulic cavitation generator, the expanded graphite in the solution is peeled off under the action of cavitation force, the cavitation treatment is repeated, and then filtered and dried to obtain nanographite microsheets;
[0029] The nanographite flakes described in step 4 have a lateral size of 1 μm to 200 μm, a longitudinal size of 50 nm to 200 nm, and a surface area of 45 m 2 / g~80m 2 / g.
[0030] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the expandable graphite described in step 1 is low-sulfur or sulfur-free expandable graphite with an expansion volume of 250 mL / g to 350 mL / g and a carbon content of more than 99.5%. The other steps are the same as those in specific embodiment 1.
[0031] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the drying temperature in step 1 is 60° C. to 80° C. and the drying time is 20 h to 24 h. The other steps are the same as those in specific implementation method 1 or 2.
[0032] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the power of the microwave treatment in step 2 is 800W to 900W, and the time of the microwave treatment is 30s to 60s. The other steps are the same as those of specific embodiments 1 to 3.
[0033] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the outlet pressure of the turbine-type hydrodynamic cavitation generator described in step 4 is 1kg to 2kg. The other steps are the same as those of specific embodiments 1 to 4.
[0034] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that the rotation speed of the turbine-type hydrodynamic cavitation generator described in step 4 is 1500r / min to 2500r / min. The other steps are the same as those of specific implementation methods 1 to 5.
[0035] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the nanographite flakes are used to prepare graphite flake / ZnNiMn-LDH composite materials. The other steps are the same as those of specific embodiments 1 to 6.
[0036] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the preparation method of the graphite microsheet / ZnNiMn-LDH composite material is specifically completed according to the following steps:
[0037] 1. Dissolve the precipitant in anhydrous ethanol to obtain solution A;
[0038] 2. dissolving zinc salt, nickel salt and manganese salt in anhydrous ethanol to obtain solution B;
[0039] 3. Add solution B to solution A, stir evenly, then add sodium chloride solution, stir and react at 60°C to 80°C for 6h to 10h to obtain ZnNiMn-LDH dispersion;
[0040] 4. dispersing the nano-graphite flakes into deionized water to obtain a nano-graphite flake solution;
[0041] 5. Add the nanographite microplatelet solution dropwise to the ZnNiMn-LDH dispersion, stir for a period of time, and then freeze-dry to obtain the ZnNiMn-LDH dispersion. The other steps are the same as those in the first to seventh embodiments.
[0042] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the precipitant described in step 1 is ammonium carbonate or ammonium bicarbonate; the mass ratio of the precipitant described in step 1 to the volume ratio of anhydrous ethanol is (0.2g-0.4g):(20mL-40mL); the zinc salt described in step 2 is zinc chloride, zinc nitrate or zinc acetate; the nickel salt described in step 2 is cobalt chloride, cobalt acetate or cobalt sulfate; the manganese salt described in step 2 is manganese chloride, manganese acetate or manganese sulfate; the molar ratio of zinc element, nickel element and manganese element in solution B described in step 2 is (8-10):(2-6):(1-4); the concentration of zinc element in solution B described in step 2 is 0.15mol / L-0.4mol / L. The other steps are the same as specific embodiments 1 to 8.
[0043] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that: the preparation method of the sodium chloride solution described in step 3 is: dissolving 2g to 4g of sodium chloride in 30mL to 50mL of boiling deionized water to obtain a sodium chloride solution; the volume ratio of solution A, solution B and sodium chloride solution described in step 3 is (20mL to 40mL): 20mL: (30mL to 50mL); the concentration of the nanographite microplatelet solution described in step 4 is 1mg / mL to 2mg / mL; the volume ratio of the nanographite microplatelet solution described in step 5 to the ZnNiMn-LDH dispersion is 50mL: (80mL to 100mL); the stirring time described in step 5 is 10h to 12h; the freeze-drying time is 30h to 40h, and the freeze-drying temperature is -40℃ to -20℃. The other steps are the same as specific embodiments 1 to 9.
[0044] The following examples are used to verify the beneficial effects of the present invention:
[0045] Embodiment 1: A method for preparing nanographite microsheets by hydrodynamic cavitation is specifically completed by the following steps:
[0046] 1. Using expandable graphite as a raw material, drying the expandable graphite to obtain dry expandable graphite;
[0047] The expandable graphite described in step 1 is sulfur-free expandable graphite with an expansion volume of 250 mL / g and a carbon content of more than 99.5%;
[0048] The drying temperature in step 1 is 80°C and the drying time is 24h;
[0049] 2. Put the dried expandable graphite into a microwave oven and perform microwave treatment for a period of time to obtain expanded graphite;
[0050] The power of the microwave treatment in step 2 is 800 W, and the time of the microwave treatment is 50 s;
[0051] 3. Mix the expanded graphite, deionized water and additives evenly to obtain a suspension solution;
[0052] The mass ratio of deionized water to expanded graphite described in step 3 is 50:1;
[0053] The auxiliary agent described in step 3 is polyethylene glycol;
[0054] The mass ratio of the additive and the expanded graphite described in step 3 is 1:1;
[0055] Fourth, adding the suspension solution into a turbine hydraulic cavitation generator, adjusting the outlet pressure and speed of the turbine hydraulic cavitation generator, the expanded graphite in the solution is peeled off under the action of cavitation force, the cavitation treatment is repeated, and then filtered and dried to obtain nanographite microsheets;
[0056] The outlet pressure of the turbine hydrodynamic cavitation generator described in step 4 is 1.5 kg;
[0057] The speed of the turbine hydraulic cavitation generator described in step 4 is 2000r / min;
[0058] The nanographite flakes described in step 4 have a lateral size of 50 μm to 100 μm, a longitudinal size of 80 nm to 120 nm, and a surface area of 70 m 2 / g~75m 2 / g.
[0059] Application Example 1: A method for preparing a graphite microplatelet / ZnNiMn-LDH composite material using the nanographite microplatelets prepared in Example 1 is specifically completed by the following steps:
[0060] 1. Dissolve the precipitant in anhydrous ethanol to obtain solution A;
[0061] The precipitant described in step 1 is ammonium carbonate;
[0062] The mass ratio of the precipitant described in step 1 to the volume ratio of anhydrous ethanol is 0.2 g:30 mL;
[0063] 2. dissolving zinc salt, nickel salt and manganese salt in anhydrous ethanol to obtain solution B;
[0064] The zinc salt described in step 2 is zinc chloride;
[0065] The nickel salt described in step 2 is cobalt chloride;
[0066] The manganese salt described in step 2 is manganese chloride;
[0067] The molar ratio of zinc, nickel and manganese in the solution B described in step 2 is 10:3:3;
[0068] The concentration of zinc in solution B described in step 2 is 0.4 mol / L;
[0069] 3. Add solution B to solution A, stir evenly, then add sodium chloride solution, stir and react at 80°C for 10 hours to obtain ZnNiMn-LDH dispersion;
[0070] The preparation method of the sodium chloride solution described in step 3 is: dissolving 3 g of sodium chloride in 30 mL of boiling deionized water to obtain a sodium chloride solution;
[0071] The volume ratio of solution A, solution B and sodium chloride solution described in step 3 is 30mL:20mL:30mL;
[0072] 4. dispersing the nano-graphite flakes into deionized water to obtain a nano-graphite flake solution;
[0073] The concentration of the graphite nanosheet solution in step 4 is 1.5 mg / mL;
[0074] 5. Add the nanographite microsheet solution dropwise into the ZnNiMn-LDH dispersion, stir for a period of time, and then freeze-dry to obtain the ZnNiMn-LDH dispersion;
[0075] The volume ratio of the nanographite microplatelet solution and the ZnNiMn-LDH dispersion described in step 5 is 50mL:80mL;
[0076] The stirring time in step 5 is 10 hours; the freeze-drying time is 40 hours, and the freeze-drying temperature is -30°C.
[0077] To verify the electrochemical capacitance of the graphite microsheet / ZnNiMn-LDH composite material prepared in Example 1, a constant current charge and discharge test was performed at a current density of 1 A / g and a potential range of 0 to 0.16 V; through the following formula C=(I*Δt) / (m*ΔV), where C(F / g) is the specific capacity of the electrode, I(A) is the current during the discharge process, Δt(s) is the discharge time, and ΔV(V) is the potential window, it can be calculated that the specific capacitance of the graphite microsheet / ZnNiMn-LDH composite material prepared in Example 1 can reach 1958 F / g.
Claims
1. A method for preparing nanographite flakes by hydrodynamic cavitation, characterized in that The method is specifically completed according to the following steps:
1. Using expandable graphite as a raw material, drying the expandable graphite to obtain dry expandable graphite; 2. Put the dried expandable graphite into a microwave oven and perform microwave treatment for a period of time to obtain expanded graphite; 3. Mix the expanded graphite, deionized water and additives evenly to obtain a suspension solution; The mass ratio of deionized water to expanded graphite in step 3 is (45-55):1; The auxiliary agent described in step 3 is anhydrous ethanol or polyethylene glycol; The mass ratio of the additive and the expanded graphite described in step 3 is (0.5-2):1; Fourth, adding the suspension solution into a turbine hydraulic cavitation generator, adjusting the outlet pressure and speed of the turbine hydraulic cavitation generator, the expanded graphite in the solution is peeled off under the action of cavitation force, the cavitation treatment is repeated, and then filtered and dried to obtain nanographite microsheets; The nanographite flakes described in step 4 have a lateral size of 1 μm to 200 μm, a longitudinal size of 50 nm to 200 nm, and a surface area of 45 m 2 / g~80m 2 / g.
2. The method for preparing nanographite flakes by hydrodynamic cavitation according to claim 1, characterized in that The expandable graphite described in step 1 is low-sulfur or sulfur-free expandable graphite with an expansion volume of 250 mL / g to 350 mL / g and a carbon content of more than 99.5%.
3. The method for preparing nanographite flakes by hydrodynamic cavitation according to claim 1, characterized in that The drying temperature in step 1 is 60° C. to 80° C., and the drying time is 20 h to 24 h.
4. The method for preparing nanographite flakes by hydrodynamic cavitation according to claim 1, characterized in that The power of the microwave treatment in step 2 is 800W to 900W, and the time of the microwave treatment is 30s to 60s.
5. The method for preparing nanographite flakes by hydrodynamic cavitation according to claim 1, characterized in that The outlet pressure of the turbine-type hydraulic cavitation generator described in step 4 is 1kg to 2kg.
6. The method for preparing nanographite flakes by hydrodynamic cavitation according to claim 1, characterized in that The rotation speed of the turbine hydraulic cavitation generator described in step 4 is 1500r / min to 2500r / min.
7. The use of the nanographite microsheets prepared by the preparation method as claimed in claim 1, characterized in that The nano graphite microsheets are used to prepare graphite microsheet / ZnNiMn-LDH composite materials.
8. The use of the nanographite microsheets prepared by the preparation method according to claim 7, characterized in that The preparation method of the graphite microsheet / ZnNiMn-LDH composite material is specifically completed according to the following steps:
1. Dissolve the precipitant in anhydrous ethanol to obtain solution A; 2. dissolving zinc salt, nickel salt and manganese salt in anhydrous ethanol to obtain solution B; 3. Add solution B to solution A, stir evenly, then add sodium chloride solution, stir and react at 60°C to 80°C for 6h to 10h to obtain ZnNiMn-LDH dispersion; 4. dispersing the nano-graphite flakes into deionized water to obtain a nano-graphite flake solution; 5. Add the nano-graphite microsheet solution dropwise into the ZnNiMn-LDH dispersion, stir for a period of time, and then freeze-dry to obtain the ZnNiMn-LDH dispersion.
9. The use of the nanographite microsheets prepared by the preparation method according to claim 8, characterized in that The precipitant described in step one is ammonium carbonate or ammonium bicarbonate; the mass ratio of the precipitant described in step one to anhydrous ethanol is (0.2g-0.4g):(20mL-40mL); the zinc salt described in step two is zinc chloride, zinc nitrate or zinc acetate; the nickel salt described in step two is cobalt chloride, cobalt acetate or cobalt sulfate; the manganese salt described in step two is manganese chloride, manganese acetate or manganese sulfate; the molar ratio of zinc element, nickel element and manganese element in solution B described in step two is (8-10):(2-6):(1-4); the concentration of zinc element in solution B described in step two is 0.15mol / L-0.4mol / L.
10. Application of the nanographite microsheets prepared by the preparation method according to claim 8, characterized in that The preparation method of the sodium chloride solution described in step 3 is as follows: 2g to 4g of sodium chloride is dissolved in 30mL to 50mL of boiling deionized water to obtain a sodium chloride solution; the volume ratio of solution A, solution B and sodium chloride solution described in step 3 is (20mL to 40mL): 20mL: (30mL to 50mL); the concentration of the nanographite microplatelet solution described in step 4 is 1mg / mL to 2mg / mL; the volume ratio of the nanographite microplatelet solution described in step 5 to the ZnNiMn-LDH dispersion is 50mL: (80mL to 100mL); the stirring time described in step 5 is 10h to 12h; the freeze-drying time is 30h to 40h, and the freeze-drying temperature is -40°C to -20°C.